Analysis of the Position, Characteristics and Purpose of Human Life in the Qur'an - Nabila Istiqoma; Alisia Fadillah Firdaust (Aslama: Journal of Islamic Studies, 2024)
The purpose of writing this article is to find out the Position, Characteristics and Purpose of Human Life in the Qur'an. The method used in this article is qualitative with a literature study approach, in the technique of reviewing and concluding various sources of literature that are relevant to the research topic. The topic raised in this study is Analyzing the Position, Characteristics, and Purpose of Human Life in the Qur'an. The sources of literature used are books, e-books, journals, articles, and trusted websites. The results of this article are the position of humans in the Qur'an covering various aspects that emphasize the role and responsibility of humans as creatures created by Allah SWT. The position of humans as caliphs on earth, human characteristics are divided into several, namely: Al-Basyar, Al-Insan, Al-Naas, Al-Ins. The purpose of human life is worship and his position is caliph. While the task of humans in the Islamic view is the prosperity of the earth by manifesting God's potential in himself.